Pengaruh Kinerja Keuangan dan Kebijakan Dividen terhadap Nilai Perusahaan pada Perusahaan Sektor Pertambangan di Bursa Efek Indonesia - Jenny Sutrisna Waruwu; Hendrajaya Hendrajaya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), Debt-to-Equity Ratio (DER), Earnings Per Share (EPS), and Dividend Payout Ratio (DPR) on company value as measured by Tobin's Q. The problem focuses on how these financial factors affect company valuation. In order to approach this problem, theoretical references from financial management and company value theory are used. Data were collected through company financial reports and analyzed quantitatively using multiple linear regression with normality, multicollinearity, and ANOVA tests.This study concludes that ROE and EPS have a positive and significant effect on Tobin's Q, indicating that equity profitability and earnings per share can increase company value. Conversely, DER and DPR have a negative and significant effect on Tobin's Q, indicating that high debt levels and large dividend payments can reduce company valuation. Meanwhile, ROA does not have a significant effect on Tobin's Q. This result implies that companies need to focus on increasing equity profitability and earnings per share, maintaining a balanced capital structure, and designing an optimal dividend policy to increase the company's value in the eyes of investors.